Contextual Teaching and Learning Model: Explosion Box Media on Learning Activity in Elementary School Students' IPAS Subjects - Khazanah, Umi Muslikhatul; Baharudin, Baharudin; Yanti, Yuli (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Fourth graders' low learning engagement in elementary schools can hinder learning, especially in Natural and Social Sciences (IPAS) subjects that require contextual understanding. We need innovative learning techniques and media to engage pupils. Thus, this study examines how the Contextual Teaching and Learning (CTL) methodology and Explosion Box media affect fourth graders' IPAS learning in elementary school. This study uses a quantitative approach with a quasi-experimental design in a nonequivalent control group posttest-only format. The sample consisted of 40 students divided into experimental and control classes at elementary school 3 Way Galih. Learning activity data were collected using a validated and reliable questionnaire. Data analysis was carried out using an independent sample t-test. The results showed a significant difference in learning activity between the experimental and control groups, with a Sig. (2-tailed) value = 0.000 < 0.05 and a t-count value of 4.965 > t-table 1.685. These results show that the CTL model with Explosion Box media boosts student learning. This medium creates an interactive, contextual, and engaging learning environment, encouraging student participation. Effective learning model recommendations come from this research. IPAS teachers can use the CTL model and Explosion Box media to motivate, engage, and contextualize elementary school pupils, supporting holistic educational goals.